2016
DOI: 10.9734/bjast/2016/24437
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectric Characterization of a Dye-sensitized Solar Cell Based on Natural Pigment Extracted from Roselle (Hibiscus sabdariffa) Flower and TiO2 Nanoparticles

Abstract: Dye-sensitized solar cell (DSSC) was fabricated using natural dye extracted from Roselle flower. The sensitization performance related to interaction between the dye and titanium dioxide (TiO 2 ) surface was evaluated under 100 mWcm -2 light intensity. The DSSC based on the Hibiscus sabdariffa organic dye gave a short-circuit current density (J sc ) of 0.0259 mAcm -2, open-circuit voltage (V oc ) of 0.432 V and fill factor (FF) of 0.594, yielding an overall solar conversion efficiency (η) of 0.0067%. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Nishantha et al [189] studied the Kopsia flavida fruit, found the anthocyanin dye used in DSSC and reported the performance of DSSC that included I sc = 1.2 mAcm À 2 , V oc = 0.520 V and FF = 0.620. Danladi et al [95] manufactured DSSC applying anthocyanin dye extracted from the roselle flower and reported performance including I sc = 0.0259 mAcm À 2 , V oc = 0.432 V, FF = 0.594 and η = 0.0067 %. Alhamed et al [98] studied on raspberries, hibiscus, chlorophyll anthocyanin dyes and reported the performance of DSSC with I sc = 0.6 mAcm À 2 and V oc = 0.42 V, FF = 0.60, η = 3.04 %.…”
Section: Anthocyaninsmentioning
confidence: 99%
“…Nishantha et al [189] studied the Kopsia flavida fruit, found the anthocyanin dye used in DSSC and reported the performance of DSSC that included I sc = 1.2 mAcm À 2 , V oc = 0.520 V and FF = 0.620. Danladi et al [95] manufactured DSSC applying anthocyanin dye extracted from the roselle flower and reported performance including I sc = 0.0259 mAcm À 2 , V oc = 0.432 V, FF = 0.594 and η = 0.0067 %. Alhamed et al [98] studied on raspberries, hibiscus, chlorophyll anthocyanin dyes and reported the performance of DSSC with I sc = 0.6 mAcm À 2 and V oc = 0.42 V, FF = 0.60, η = 3.04 %.…”
Section: Anthocyaninsmentioning
confidence: 99%
“…Natural dyes, including plant colorants such as anthocyanins [4][5][6][7][8][9][10][11][12], betalains [13][14][15][16], chlorophyll [17][18][19][20][21] and carotenoids [22][23][24], have already been targeted in many studies. For this particular work, two natural products from Peru have been used.…”
Section: A D V a N C E D O N L I N E A R T I C L Ementioning
confidence: 99%
“…The use of natural dyes have been considered as potential candidates to enhance the light response of semiconductor in active layers of solar cells, and have been demonstrated on several solar-cell materials [24][25][26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%